Comparing Transport Corridors Based on Total Economic Cost - Alwyn J. Hoffman; Crynos Mutendera; Willem C. Venter (Journal of Advanced Transportation)
This paper compares the performance of three competing corridors serving landlocked SADC countries (Beira, Dar es Salaam, and Durban) based on total economic cost from the perspective of transporters, retailers, and manufacturers. The motivation for the research is the paradox that, while Beira is closest to the hinterland served by these corridors, it attracts the least cargo. Historical research compares corridors in terms of both direct costs and time delays, but without translating time delays and variability in time delays into the economic costs experienced by corridor users. Unpredictable time delays reduce the competitiveness of cargo owners forming part of global just-in-time value chains. Our novel TEC model includes direct costs and the cost impact of delays and variability in delays and quantifies the relative contributions of ports, border posts, and road travel. The Port’s efficiency proved to be the biggest differentiator between these corridors, followed by border posts and road links. We found that while the Beira corridor has the lowest cost if only average travel time is considered, the Durban corridor proves to be the most competitive when variability in time delays is also considered, explaining why Durban enjoys the largest share of cargo transported to the landlocked hinterland.